CNR1 genotype influences HDL-cholesterol response to change in dietary fat intake. - Heidi J Silver; Kevin D Niswender; Charles D Keil; Lan Jiang; Qiping Feng; Sally Chiu; Ronald M Krauss; Russell A Wilke (PLoS ONE)
Background Success in further reducing the burden of cardiovascular disease (CVD) is threatened by the increasing prevalence of obesity-related atherogenic dyslipidemia. HDL-cholesterol (HDL-C) level is inversely correlated with CVD risk; each 1 mg/dl decrease in HDL-C is associated with a 6% reduction in risk. We previously showed that a common CNR1 haplotype, H3 (frequency 20%), is protective against the reduction in HDL-C that typically accompanies weight gain. In the present study, we extend that observation by reporting the effect of CNR1 haplotype on HDL-C response to modification of dietary fat intake in weight maintenance and weight loss. Methods Six haplotype tagging SNPs that cover the CNR1 gene locus were genotyped in 590 adults of varying body mass index (cohort 1 is 411 males with BMI 18.5-30.0 kg/m(2); cohort 2 is 71 females with BMI18.5-30.0 kg/m(2); and cohort 3 is 108 females with BMI 30-39.9 kg/m(2)). Dietary intakes were modified so that fat intake in the "high fat" condition was 15-20% greater than in the "low fat" condition, and lipid profiles were compared between carriers versus noncarriers for each of the five commonly observed CNR1 haplotypes (H1-H5). Results In normal to overweight subjects on eucaloric diets, the H3 haplotype was significantly associated with short-term high fat diet induced changes in HDL-C level in females (carriers 5.9 mg/dl>noncarriers, p = 0.007). The H3 haplotype was also significantly associated with HDL-C level after 16 weeks on high fat calorie restricted diet in obese females (carriers 6.8 mg/dl>noncarriers, p = 0.009). Conclusion Variability within the CNR1 gene locus contributes to gender-related differences in the HDL-cholesterol response to change in dietary fat intake. Functional characterization of this relationship in vitro may offer insights that potentially yield therapeutic guidance targeting dietary macronutrient composition, a direction much needed in the current epidemic of obesity.